The Influence Of Authentic Materials Content On Overcoming Linguistic Challenges In Efl Education - Ladjel, Khawla; Ladjel, Karima (Eddissi Languages Journal, 2024)
Proficiency in a particular language cannot be restricted only to the acquisition of linguistic rules. This means that language users who are eager to communicate using the target language need to reflect on the social features of the target community. This belief does not reject the fact that linguistic competence is the primary criterion, which EFL students ought to master, but it highlights the importance of integrating the social and pragmatic rules of the target contexts when learning the target language rules of grammar. In other words, learners should not acquire requisite grammar knowledge only but also attain a profound comprehension of how native speakers employ grammar rules within specific contextual frameworks (social contexts). Aligning with this perspective, the current investigation seeks to delve into the various impediments hindering students from proficiently applying their linguistic competence. Additionally, the study endeavors to ascertain whether the utilization of authentic materials can enhance students' adeptness in employing grammar rules across varying contexts. This research is conducted with second-year students enrolled in the English department at M’sila University. Using three research instruments—classroom observation, a questionnaire, and an interview—the study reveals that integrating authentic materials into grammar instruction encourages students to examine the context before deducing the general application of grammar rules. The collected data suggest that these materials facilitate a deeper understanding of how a specific grammar rule is applied diversely by native speakers in the target community.